2006
DOI: 10.1098/rspb.2005.3463
|View full text |Cite
|
Sign up to set email alerts
|

Biocomplexity in a highly migratory pelagic marine fish, Atlantic herring

Abstract: The existence of biologically differentiated populations has been credited with a major role in conferring sustainability and in buffering overall productivity of anadromous fish population complexes where evidence for spatial structure is uncontroversial. Here, we describe evidence of correlated genetic and life history (spawning season linked to spawning location) differentiation in an abundant and highly migratory pelagic fish, Atlantic herring, Clupea harengus, in the North Sea (NS) and adjacent areas. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
204
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(214 citation statements)
references
References 25 publications
9
204
0
1
Order By: Relevance
“…Using the microsatellite data for the same samples collected at Berwick and Tj me as in this study, as well as several other samples, Ruzzante et al (2006) showed that herring collected at Rü gen in the southwestern Baltic is clearly distinct from the populations in the North Sea and Skagerrak. In this study, the differentiation estimated with neutral microsatellites was stable over Abbreviations: AMOVA, analysis of molecular variance; MHC, major histocompatibility complex; mtDNA, mitochondrial DNA.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Using the microsatellite data for the same samples collected at Berwick and Tj me as in this study, as well as several other samples, Ruzzante et al (2006) showed that herring collected at Rü gen in the southwestern Baltic is clearly distinct from the populations in the North Sea and Skagerrak. In this study, the differentiation estimated with neutral microsatellites was stable over Abbreviations: AMOVA, analysis of molecular variance; MHC, major histocompatibility complex; mtDNA, mitochondrial DNA.…”
Section: Discussionsupporting
confidence: 53%
“…However, as long as selection pressure is temporally stable (decades-centuries), genetic markers influenced by selection, such as Cpa112, can be of use in detecting population structure on ecological time scales, where neutral loci have not yet diverged substantially. Selected loci may be particularly useful in genetic stock identification based on individual assignment and as markers for population origin in mixed-stock analysis (see Nielsen et al, 2009a, p. 3136), for example, MHC in Pacific sockeye salmon (Beacham et al, 2005), the pantophysin locus in mixed stocks of coastal and oceanic cod in Lofoten, northern Norway (Wennevik et al, 2008) and Cpa112 in mixed-stock analysis of herring in the Skagerrak (Ruzzante et al, 2006). It may be preferable to use selection-influenced genetic markers with known function (Hoffmann and Willi, 2008), or with at least some knowledge of the nature of the selection pressure, for example, hemoglobin (Andersen et al, 2009), genes involved in osmoregulation (Larsen et al, 2008) and depth adaptation (Á rnason et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviated sample names are defined in Table 1 life-cycle diversity in fish (e.g. Ruzzante et al 2006, Kerr et al 2009b). Gene flow is not only a function of adult behaviors, but also of egg and larval dispersal.…”
Section: Mechanisms Of Population Structuringmentioning
confidence: 99%
“…An important consequence of species being divided into locally adapted populations that may have key roles in their local ecosystem is that an extinct local population may not easily be replaced by recruits from other areas. Indirect support for such a conclusion is found in species where extensive mixing of populations occurs during some life stage without break down of the discrete population structure-a phenomenon sometimes referred to as biocomplexity (Ruzzante et al 2006;Schindler et al 2010).…”
Section: Introductionmentioning
confidence: 99%